Respuesta :
-9*7=8(y-6.6)
You first begin with multiplying the left side in this case, and then you multiply the right side, so:
-9*7=8(y-6.6)
⬇
-63 = 8y -52.8
+52.8 +52.8
⬇
-10.2 = 8y
Divide both sides by 8, and you're left with:
y = -1.275
Hope this helps explain it a little.
You first begin with multiplying the left side in this case, and then you multiply the right side, so:
-9*7=8(y-6.6)
⬇
-63 = 8y -52.8
+52.8 +52.8
⬇
-10.2 = 8y
Divide both sides by 8, and you're left with:
y = -1.275
Hope this helps explain it a little.